Estimating load carrying capacity of single pile in residual soils - Kusuma, Mutiasani Dianmarti. (2012)
Bored piles are extensively installed in Singapore residual soils for foundation purpose. Unfortunately, traditional design of bored piles is based on properties of clays, sands, or rocks. In addition, bored piles are designed relying on base resistance (Qb) despite the fact that side resistance’s (Qs) contribution towards the total axial capacity is higher at the working load. Therefore, the design of bored piles installed in Singapore residual soils is to be optimized considering both axial capacity and economical aspect.